The Canadian Water Resource Vulnerability Index to Permafrost Thaw (CWRVIPT) - C. Spence (Arctic Science, 2020)
This study developed and applied a framework for assessing the vulnerability of pan-Canadian water resources to permafrost thaw. The national-scale work addresses a key, but neglected, information gap, as previous research has focused on small scale physical processes and circumpolar trends. The framework was applied to develop the Canadian Water Resources Vulnerability Index to Permafrost Thaw (CWRVIPT) and map the index across the Canadian North. The CWRVIPT is a linearly additive index of permafrost, terrain, disturbance, and climatic conditions and stressors that influence water budgets and aquatic chemistry. Initial results imply water resources in the western Northwest Territories and Hudson Bay Lowlands are most vulnerable to permafrost thaw; however, water resources on Banks, Victoria and Baffin Islands are also relatively vulnerable. Although terrain and permafrost sub-indices are the largest component of the CWRVIPT across a wide swath from the Mackenzie River Delta to the Hudson Bay Lowlands, the climate sub-index is most important farther north over parts of the southern portion of the Arctic Archipelago. The index can be used to identify areas of water resource vulnerability on which to focus observation and research in the Canadian North.